MECHANICS OF IMPROVING THE EFFICIENCY OF ENTERPRISES ON THE BASIS OF INNOVATION - Mamajonova, (EPRA International Journal of Research and Development (IJRD), 2024)
In this article, the mechanisms of increasing the efficiency of industrial enterprises of the country on the basis of innovations, the methods of using innovative and scientific and technical potential for economic development are comprehensively applied.